Does rail transit development gentrify neighborhoods? Evidence from Hong Kong. (January 2022) - Liang, Cong; Huang, Yaoxuan; Yip, Tsz Leung; Li, Victor Jing
Abstract: Transit-induced gentrification is a popular topic of research and a pressing concern worldwide. However, little attention is paid to the connection between rail transit development and the movement of low-income residents. To investigate this important issue, this paper studies the development of the Mass Transit Railway (MTR) in Hong Kong between 2001 and 2006, which added three new rail transit lines covering a total length of 65 km. By using census statistics at the district council constituency area (DCCA) level in a difference-in-differences approach, we find that MTR development in Hong Kong between 2002 and 2004 increased the number of advanced degree holders (Bachelor's degree and above) by 10% in the New Territories and 7.81% in the new towns and reduced the number of low-income households by 5.85% in the New Territories and 7.53% in the new towns. To confirm that these socioeconomic changes were driven by internal migration, we further use household-level data from the 5% population censuses in 2001 and 2006 in a multinomial logistic regression. The results indicate that MTR development between 2002 and 2004 was likely to induce high-educated people to move into and low-income households to move out of MTR-served areas. The results show that the New Territories and the new towns in Hong Kong underwent gentrification between 2001 and 2006. We therefore suggest that the Hong Kong government negotiate with MTR Corporation to allocate resources to develop properties for low-income families.